Accelerating the development of biological nitrification inhibition as a viable nitrous oxide mitigation strategy in grazed livestock systems - Klein, Cecile A.M. de; Bowatte, Saman; Arango, Jacobo; Cardenas, Laura M.; Chadwick, David R.; Pijlman, Jeroen; Rees, Robert M.; Richards, Karl G.; Subbarao, Guntur V.; Whitehead, David; Simon, Priscila L. (Springer, 2022)
This position paper summarizes the current understanding of biological nitrification inhibition (BNI) to identify research needs for accelerating the development of BNI as a N2O mitigation strategy for grazed livestock systems. We propose that the initial research focus should be on the systematic screening of agronomically desirable plants for their BNI potency and N2O reduction potential. This requires the development of in situ screening methods that can be combined with reliable N2O emission measurements and microbial and metabolomic analyses to confirm the selective inhibition of nitrification. As BNI-induced reductions in N2O emissions can occur by directly inhibiting nitrification, or via indirect effects on other N transformations, it is also important to measure gross N transformation rates to disentangle these direct and indirect effects. However, an equally important challenge will be to discern the apparent influence of soil N fertility status on the release of BNIs, particularly for more intensively managed grazing systems.